The Role of Islamic Religious Education Teachers in Instilling Religious Moderation Values in Generation Z - M. Agus Nurohman; Bambang Tri Wantoro; Wakib Kurniawan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This research aims to explore the strategies, teaching methods, and approaches used by IRE teachers to nurture balanced, tolerant, and inclusive religious attitudes. Generation Z is growing up in a digital era that is full of information, including diverse religious content. The biggest challenge is filtering out extreme and intolerant information. This is where the strategic role of Islamic Religious Education (PAI) teachers is needed as agents of religious moderation. This article discusses the role of PAI teachers in instilling religious moderation values such as tolerance, non-violence, and love for the country. This research uses a qualitative approach with literature studies and field observations in several junior high schools in Indonesia. The results show that teachers who can integrate moderation values in teaching materials and personal exemplars contribute significantly in shaping balanced religious understanding in students. This article offers concrete recommendations for strengthening the role of teachers in moderate religious character education.